Cytological Study of Tuberculosis in Pulmonary and Extrapulmonary Lesions in Correlation with Cartridge Based Nucleic Acid Amplification Test (CBNAAT) - Dronadula, Gayathri; Apuroopa, Murari (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: Various methods can be used for the detection of tuberculosis of which microscopy, culture and identification of the organism's DNA are known. Newly introduced Nucleic acid amplification test (NAAT) if used in combination with other tests provide improved diagnostic yield. Aims and Objectives: To diagnose tuberculosis bacilli in various cytological samples and sputum samples. To evaluate the diagnostic efficacy of combined approach of conventional smear study and and CBNAAT. Material and Methods: A Total of 50 cytology samples received in Pathology Department were studied over a period of 6 months. These included sputum (20), lymph node(22),body fluids(8).For these samples routine staining and ziehl neelsen are done and the remaining sample is sent for CBNAAT.Results are compared among AFB,CBNAAT for these samples. Sensitivity and specificity of microscopy and CBNAAT tests were calculated. Results: Out of 50 cases 31 cases were positive for smear study and 29 cases were positive for CBNAAT. Conclusion: Cytological examination of TB in association with CBNAAT is more confirmatory, sensitive and specific tool for the early diagnosis of MTB in variety of clinical samples.